(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is about the dialect phraseological units with the components-loanwords, which were recorded in works of art of L. Martovich, V. Stefanik, G. Hotkevich, M.Cheremshina. Interrelations of Ukrainian with other national languages, ways of loan of words and the stylistic potential of dialect phraseological units are investigated.